From Classical to Virtual: Analysis of the Value and Impact of Education Policy Responding to the Covid-19 Pandemic - Suyuthi, Ahmad (Indonesian Journal of Political Studies, 2022)
The Covid-19 pandemic has disrupted various aspects of life. During the coronavirus outbreak, the two most affected essential sectors were the economic and education sectors. This article aims to analyze education policy in Indonesia in response to the global pandemic. This research managed to find that education policy becomes public policy because it is realized to the public directly. In the formulation stage of education policy, the government, in this case, the Ministry of Education, collaborates with multi-stakeholders to ensure the community's fundamental right to obtain an education. However, it was found that education policy does not maximally see the disparity of society, so the community faces various obstacles because the policy is not balanced with the preparation of adequate digital infrastructure. So many people do not enjoy government subsidies. In addition, it can be concluded that national education policy uses an interactive-participatory model that shows collaboration with interested agencies to realize policies in the public domain in education implementation jointly.